AZSCHED computer software for irrigation scheduling - Clark, Lee J., author; Slack, Donald C., author; Martin, Edward, author; Fox, Fred A., Jr., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1992)
AriZona irrigation SCHEDuling (AZSCHED) software provides irrigation scheduling information on 15 crops in up to 60 fields, with different planting dates, soil types and irrigation strategies. AZSCHED uses the soil water balance method for irrigation scheduling with water-use being estimated by a Modified Penman equation and heat-unit based crop coefficients. The weather data are supplied by localized historical weather data supplemented with real-time weather data. Weather data can be input manually or from computer files. An irrigation prediction report is generated in which fields being scheduled are prioritized by date and the amount of water needed to restore the soil profile to field capacity. The program was written in Quick Basic and compiled into a compact, user-friendly and attractive package.
Irrigation and water resources in the 1990's
Software for irrigation scheduling
Not digitized by CSUL Digital Services.
Presented at Irrigation and water resources in the 1990's: proceedings from the 1992 national conference held on October 5-7, 1992 in Phoenix, Arizona.